Role of S100B Serum Concentration as a Surrogate Outcome Parameter After Mechanical Thrombectomy. (30th November 2021) - Luger, Sebastian; Koerbel, Kimberly; Martinez Oeckel, Ariane; Schneider, Hauke; Maurer, Christoph J.; Hintereder, Gudrun; Wagner, Marlies; Hattingen, Elke; Foerch, Christian
Abstract : Background and Objectives: To establish serum concentration of protein S100B as an objective biomarker surrogate for astroglial tissue damage after mechanical thrombectomy in patients with acute ischemic stroke. Methods: This prospective 2-center study recruited patients with acute middle cerebral artery infarctions caused by large vessel occlusion treated with mechanical thrombectomy. Blood samples were collected at day 2 after intervention and analyzed for S100B serum concentrations using ELISA techniques. Infarct size was determined on follow-up brain imaging and functional outcome according to modified Rankin Scale (mRS) was assessed at 90 days. Results: A total of 171 patients were included (mean age ± SD: 70 ± 14 years, 42% female). S100B levels correlated with infarct size. Median S100B concentrations at day 2 after intervention were lower in patients with favorable outcome (mRS score 0–1) at 90 days compared to patients with unfavorable outcome (mRS score 2–6) (median 0.10 µg/L [interquartile range 0.07–0.14] vs 0.20 µg/L [0.11–0.48], p < 0.001). Younger age (odds ratio [OR] 1.120 [confidence interval (CI) 1.068–1.174]; p < 0.001), lower National Institutes of Health Stroke Scale score 24 hours after symptom onset (OR 1.232 [CI 1.106–1.372]; p < 0.001), and lower S100B serum concentrations (OR 1.364 [CI 1.105–1.683]; p = 0.004) were independently associated with a favorable outcome. S100B was able to eliminate the lateralization bias associated with the use of mRS for functional outcome assessment at 90 days after stroke. Discussion: S100B serum concentrations after mechanical thrombectomy indicate the extent of ischemic tissue damage. This can be assessed rapidly, independent of brain imaging and clinical outcome scales. Following prospective validation in further studies, this may provide an objective surrogate outcome measure both in clinical routine and interventional trials. Classification of Evidence: This study provides Class I evidence that S100B 2 days following mechanical thrombectomy for acute ischemic stroke accurately distinguishes favorable from unfavorable functional outcome.